Effect of Sowing Date and Intra-Row Spacing on Growth and Yield of Groundnut at El Rahad Agricultural Scheme - A. Babiker, Elfadil (Gezira Journal of Agricultural Science, 2021)
The effects of sowing date and intra-row spacing on growth and yield of groundnut ( Arachis hypogaea L.) were evaluated over a 3- year period in the irrigated Rahad Scheme. The main effects of sowing date and intra-row spacing were significant but their interactions were not. Late sowing in August and September resulted in small plants with fewer pods, low biological and pod yields due to their development under the low temperatures of November, December and January. On the other hand, high number of pods was produced per plant at wide intra-row spacing but most of the pods were immature with poor shelling percentage and low 100-seed weight. This was attributed to the uneven maturity of groundnut at harvest where pods were initiated over a longer period of time particularly in the low plant population. Early sowing (June) and the high plant population (250000 plants/ ha) proved to be essential package components for the alternately branched variety (MH383) under irrigated vertisol of El Rahad Agricultural Scheme.